INTEGRATING LOCAL CONTENT CULTURE THROUGH FOLKTALE AS A LANDMARK IN ELT - Gustianing, Defy (Universitas Aisyah Pringsewu, 2022)
The objective of the study to: (1) investigate the development of students’ cultural awareness by integrating a folktale as a landmark in the learning process; (2) know the learners’ perceive their English language learning toward integrating a folktale as a landmark in the learning process. Culture is the patterns which have explicit and implicit view. The essential view of culture consists of traditional, ideas, values, behavior, and cultural product. Nowdays, Indonesian cultural beyond the imagination to the world in various field. The cultural context that will describe is in educational field. There are three points as the fact which related to the English language learning and teaching process toward the learners. The majority of students lack cultural understanding, especially when it comes to local traditions. Unintentionally, the students misunderstand how culture affects learning. In order for the learner to have a bad attitude about learning culture. For the continued transfer of cultural knowledge, culture and ELT are still taught as a fixed system of formal structures and universal speech functions. In conclusion, this study demonstrates the positive effects of using Indonesian folktales as ELT content at the primary level in Indonesia. The participating teachers are of the opinion that exposing children to the material of such stories will help them learn English more quickly and more easily.